Az angolszász házassági jog a törzsi szokásjogok alapján - Rózsa, Csongor Ernő (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
According to Sir Maitland and Sir Pollock, the „Anglo-Saxon law is not only archaic, but offers an especially pure type of Germanic archaism”. This means that the Old-English law is free from any Roman or Christian element, thus it is inherenlty different among other Germanic customary laws. The law codes (in Old-English they are called domas) are written in their own language, unlike other Germanic tribes who wrote in Latin. Altough the Roman and Christian elements will appear in the Isle when Aethelberht changes religion, the impacts are minimal. In other words: those who want to come to know the closest one of the Germanic customary laws to the original, they should pay attention to the „lost child” of the Leges Barbarorum: the Leges Anglo-Saxonum. In my essay the questions are simple: what characterizes the legal status of a married woman and a widow? Is she an object or a person? What happens with her and her property after the death of her husband? There are answers, but they are comlicated. The provisions are obscure and are difficult to understand because their language is archaic, and the researchers are subjective to the point where we no longer knows the truth. This way there is no end of the presumptions and guesses, the literature is often contravene with itself, thus it is necessary to take a commitment in some questions. Still I think there is some kind of an objective reality I found: a woman is not less than a living person but sadly she cannot be totally equivalent with men (and her husband).